IN-SERVICE TRAINING AND ITS EFFECTS ON CLASSROOM PROCESSES : PERCEPTIONS OF SCHEDULED CASTE TEACHERS IN PALI AND NAGAUR DISTRICTS (RAJASTHAN) - Soni, R.B.L. (THE PRIMARY TEACHER, 2011)
The perceptions of Scheduled Caste (SC) teachers towards in-service training programme and its effects on classroom processes were studied in Pali and Nagaur districts of Rajasthan. The samples comprising 26 SC teachers from 14 schools in Pali district and 17 SC teachers from 15 schools in Nagaur district were selected through purposive sampling. Interview and observation schedules were developed for collection of data. The results of the study indicated that inservice training programmes need drastic improvement in terms of contents, selection of resource persons and delivery mechanism if quality of classroom processes is to be improved